2010
DOI: 10.1016/j.ajhg.2010.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in PVRL4, Encoding Cell Adhesion Molecule Nectin-4, Cause Ectodermal Dysplasia-Syndactyly Syndrome

Abstract: Ectodermal dysplasias form a large disease family with more than 200 members. The combination of hair and tooth abnormalities, alopecia, and cutaneous syndactyly is characteristic of ectodermal dysplasia-syndactyly syndrome (EDSS). We used a homozygosity mapping approach to map the EDSS locus to 1q23 in a consanguineous Algerian family. By candidate gene analysis, we identified a homozygous mutation in the PVRL4 gene that not only evoked an amino acid change but also led to exon skipping. In an Italian family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
140
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(154 citation statements)
references
References 44 publications
10
140
0
1
Order By: Relevance
“…Close contacts between infected immune cells and epithelial cells create opportunities for cell-cell fusion upon binding of the viral hemagglutinin expressed on the surfaces of infected immune cells to nectin-4 expressed at adherens junctions of epithelial cells. While nectin-4 is expressed at high levels only in the human trachea, its expression is also detected in other tissues, including the lungs and skin (17,18). Infected immune cells could spread the infection to all of these tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Close contacts between infected immune cells and epithelial cells create opportunities for cell-cell fusion upon binding of the viral hemagglutinin expressed on the surfaces of infected immune cells to nectin-4 expressed at adherens junctions of epithelial cells. While nectin-4 is expressed at high levels only in the human trachea, its expression is also detected in other tissues, including the lungs and skin (17,18). Infected immune cells could spread the infection to all of these tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Two groups recently identified the longsought epithelial receptor (EpR) as nectin-4 (N4) (15,16). Nectin-4 is expressed preferentially in the tracheobronchial epithelium (17,18), the ideal location for aerosol droplet release through coughing and sneezing (15,19), accounting for the observation that MV is the human virus with the highest reproductive rate (20).…”
mentioning
confidence: 99%
“…Both of these are autosomal recessive disorders that are clinically characterized by unusual facial appearance, dental anomalies, hypotrichosis, palmoplantar hyperkeratosis and onychodysplasia, syndactyly, cleft lip or palate, and in some cases, mental retardation. Mutations in human PVRL4 (which encodes nectin-4) that result in the failure of nectin-4 binding to nectin-1 cause an ectodermal dysplasiasyndactyly syndrome that is characterized by the combination of hair and tooth abnormalities, alopecia and cutaneous syndactyly (Brancati et al, 2010). Recent genome-wide association studies of various populations, including Japanese and African Americans, have shown a genetic association between singlenucleotide polymorphisms (SNPs) in PVRL2 (which encodes nectin-2) and late-onset alzheimer's disease (Harold et al, 2009;Logue et al, 2011;Takei et al, 2009), and mutations in PVRL3 (which encodes nectin-3) are associated with human ocular disease and congenital ocular defects (Lachke et al, 2012).…”
Section: Nectins In Human Diseasesmentioning
confidence: 99%
“…Furthermore, MV sometimes persists in the central nervous system (CNS) and causes a fatal degenerative disease, subacute sclerosing panencephalitis (SSPE), several years after acute measles (1,(18)(19)(20). In SSPE, MV appears to infect neuronal cells independently of SLAM and nectin 4, since neither SLAM nor nectin 4 is expressed at significant levels in the human CNS (21)(22)(23). Thus, how MV infects neuronal cells and causes the disease has not been well defined.…”
mentioning
confidence: 99%